THE EFFECT OF THE RADEC MODEL ON STUDENTS' READING COMPREHENSION - Rizkia Nur Rahma; Hetilaniar; Marleni (Universitas PGRI Palembang, 2024)
This research was motivated by students' lack of understanding in understanding the meaning of reading texts so that during the learning process students were not able to answer questions correctly, this is the cause of the lack of reading comprehension skills in students in class III. This research aims to find out how the RADEC model influences students' reading comprehension abilities in class III of SD Negeri 5 Palembang. The sample for this research was all class III students consisting of two classes using a saturated sampling technique, namely, class III A and III B students at SD Negeri 5 Palembang. This research uses Quasi Experimental research methods. The method for collecting data on student activities is through observation and documentation, while data on students' reading comprehension abilities is collected using essay tests. With a Nonequivalent Control Group Design. The research data analysis method uses quantitative analysis using the Independent Sample T-test. The results showed that the posttest average for the experimental class was 82.69 and the control class was 68.38. The calculation results obtained = 7.321 and = 1.680 with a significance level = 0.05. Meaning, it can be concluded that it is rejected and accepted. Shows that there is an influence of the RADEC model on the reading comprehension abilities of students in class III of SD Negeri 5 Palembang.